2017
DOI: 10.1039/c6sm02174c
|View full text |Cite
|
Sign up to set email alerts
|

The ionic strength dependent zeta potential at the surface of hexadecane droplets in water and the corresponding interfacial adsorption of surfactants

Abstract: An anomalous maximum in the ionic strength dependent electrophoretic mobility curves has been observed in previous reports from particles dispersed in colloids. This maximum has been considered anomalous because it is contradictory with the Gouy-Chapman model. The existence of such a maximum has been attributed to specific ionic adsorption, a hairy layer at the surface, or the effect of the anomalous change of surface conductivity in different studies. It was also pointed out that the O'Brien-White approach ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 76 publications
0
36
0
Order By: Relevance
“…The geometric constrains [58−60] from the continuous order-disorder transition of the spatial conformation of the interfacial carboxyl chains sterically hinder the electrostatic attraction interaction between the positively charged D289 molecules and the negatively charged surface of PDAs vesicles due to the decrease in the adsorption density of D289 molecules at the surface of PDAs vesicles with the increased UV irradiation. Besides, the chain-chain interaction is known to significantly influence the molecular energetics at the interfaces [40,44]. The interaction between the D289 molecules and the carboxyl chains of PDAs may be weakened by the ragged distortion and interleaving of the carboxyl chains in chromatic transitions from monomer to blue-to-purple-to-red forms as shown in FIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometric constrains [58−60] from the continuous order-disorder transition of the spatial conformation of the interfacial carboxyl chains sterically hinder the electrostatic attraction interaction between the positively charged D289 molecules and the negatively charged surface of PDAs vesicles due to the decrease in the adsorption density of D289 molecules at the surface of PDAs vesicles with the increased UV irradiation. Besides, the chain-chain interaction is known to significantly influence the molecular energetics at the interfaces [40,44]. The interaction between the D289 molecules and the carboxyl chains of PDAs may be weakened by the ragged distortion and interleaving of the carboxyl chains in chromatic transitions from monomer to blue-to-purple-to-red forms as shown in FIG.…”
Section: Discussionmentioning
confidence: 99%
“…During the experiments the size of the vesicle kept relatively stable with standard deviation of the average diameter less than 10%, and the polydispersity index (PDI) less than 0.2. Zeta potential of vesicles was determined by the mobility values according to the Smoluchowski equation, which is normally applied at cases other than very low ionic strength [40,49].…”
Section: Electrophoretic Mobility Measurement and Zeta Potential Cmentioning
confidence: 99%
“…After each measurement, the sample was transferred back into the initial solution (to keep a nearly constant volume of ELP/DNA complex solution) before the next addition of ELP. The electrophoretic mobility of the particles was measured by the instrument and converted into ζpotential value using the classical Smoluchowski expression [66]. In a set of experiments, Sodium dodecyl sulfate (SDS) was used to test the stability of DNA/ELP complexes [68].…”
Section: ζ-Potential Measurementsmentioning
confidence: 99%
“…More recently, the possibility of emulsion-stabilized drops having the higher of two ζ -potentials predicted by the standard electrokinetic model was rejected on the basis that they are unphysically high (Yang et al 2017). However, such a claim is Dynamic mobility of surfactant-stabilized nano-drops 895 A14-3 controversial, as other electrokinetic studies have expressly identified such interfaces as bearing significantly higher charge (Hunter & O'Brien 1997).…”
Section: Introductionmentioning
confidence: 99%